علاقة الوعي الذاتي في جودة الحياة لمعلمات رياض الاطفال - Kazem Hadi, Ikram (Journal of College of Education, 2022)
Summary The research aimed to investigate the relationship between the level of self-awareness and the quality of life for kindergarten teachers in the General Directorate of Education in Baghdad, Karkh /1 . To achieve the goal of the current research, the researcher created a scale to identify the level of self-awareness relationship and the related quality of life based on theories and open questionnaire. The final draft of the scale is illustrated in number of items, which are (39) total items. The researcher obtained indicators that approve the validity of the scale by presenting it to a group of experts who are specialized in childhood and psychology. The validity of the scale was verified through some of its indicators. After verifying the psychometric properties of the scale, it was applied to the research sample, which involve (200) kindergarten teachers, who were selected by a simple random method. After the data was collected and analyzed statistically using appropriate statistical methods such as (one-sample t-test, Pearson correlation coefficient). The results showed that there is a direct relationship between self-awareness and the consequent quality of life for kindergarten teachers. Considering the results, the researcher presented some recommendations and suggestions.